2017
DOI: 10.1111/pin.12564
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of lanthanum dosage with lanthanum deposition in the gastroduodenal mucosa of dialysis patients

Abstract: Lanthanum (La) deposition has been observed in gastrointestinal mucosa of dialysis patients treated with La carbonate to treat hyperphosphatemia in the 6 years since its authorization in Japan. We investigated gastrointestinal biopsies from 112 dialysis patients, and found 15 cases of histiocytic aggregation with crystalloids and one case of duodenitis with histiocyte aggregation without crystalloids in the 30 patients treated with La carbonate. No histiocytic lesions were observed in the 82 patients without L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 20 publications
(26 reference statements)
2
21
0
Order By: Relevance
“…At the present time, which has seen rapid strides in the development of omics analysis technologies, such as genome analysis, it is expected that data‐driven studies based on analysis of clinical samples will help clarify the molecular mechanisms responsible for the occurrence, progression and treatment responsiveness of diseases, thereby leading to the development of new biomarkers for diagnosis and identification of drug discovery targets . In particular, analysis of pathological tissue samples collected from the exact site of a disease, such as cancer, will be indispensable for the realization of genomic medicine …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At the present time, which has seen rapid strides in the development of omics analysis technologies, such as genome analysis, it is expected that data‐driven studies based on analysis of clinical samples will help clarify the molecular mechanisms responsible for the occurrence, progression and treatment responsiveness of diseases, thereby leading to the development of new biomarkers for diagnosis and identification of drug discovery targets . In particular, analysis of pathological tissue samples collected from the exact site of a disease, such as cancer, will be indispensable for the realization of genomic medicine …”
mentioning
confidence: 99%
“…3 In particular, analysis of pathological tissue samples collected from the exact site of a disease, such as cancer, will be indispensable for the realization of genomic medicine. [4][5][6][7][8][9][10][11][12] Besides detailed and accurate clinicopathological information about pathological tissue samples, the quality of the tissue samples itself holds the key to the success of such data-driven studies. 13,14 Appropriate collection and storage of pathological tissue samples enables reliable and high-quality analyses that can contribute to prevention and treatment of diseases.…”
mentioning
confidence: 99%
“…To explore whether SEM observation using the NanoSuit-CLEM method is useful for the diagnosis of lanthanum phosphate deposition in the gastrointestinal tract, we first performed SEM observation in six cases (cases 1-6) having a pathological record of brown pigment deposition, which were suspected as lanthanum phosphate deposition, in the H&E slides, either or both of stomach and duodenum (Figure 2a; representative images showing deposition exhibiting granular, needle-shaped, or amorphous structure), known as target organs of lanthanum phosphate deposition [8,12]. The same area was observed with the aid of the NanoSuit-CLEM method.…”
Section: Nanosuit-clem Methods Combined With Sem-eds Is Useful For Thementioning
confidence: 99%
“…Lanthanum carbonate binds with ingested phosphate to form insoluble complexes in the digestive tract, which are excreted with the feces [2]. However, recent reports have reported that small amounts of lanthanum phosphate are deposited in the stomach and duodenum in patients treated with lanthanum carbonate [3][4][5][6][7][8][9][10][11][12][13][14][15]. The lanthanum phosphate deposition is frequently observed especially in the stomach [6,14], and is suggested to be associated with some pathological conditions such as intestinal metaplasia and foveolar hyperplasia [5,7,8,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation